Nurses' Sleep Quality and Its Influencing Factors During the First Explosive COVID‐19 Outbreak in Zhejiang, China, After the Relaxation of Epidemic Prevention and Control Measures: A Multicentre Cross‐Sectional Study - Lifen Lu; Di Sheng; Yaling Zhu; Xiaowei Xia; Guanghui Chen; Jiali Liang; Xiulan Shen; Gui Zheng (Nursing Open)
ABSTRACT Aim To investigate the sleep quality and its influencing factors among nurses in hospitals in Zhejiang, China, during the first explosive COVID‐19 outbreak following the relaxation of prevention and control measures. Design A multicentre cross‐sectional study. Methods Between 10 January and 20 January 2023—approximately 1 month after the policy was loosened—a total of 573 nurses from tertiary and community hospitals in Zhejiang participated in an online, self‐administered survey. The participants were recruited using convenience sampling, and the survey was distributed via the WeChat platform. The survey included a general information form; the Self‐Rating Scale of Sleep (SRSS); the Depression, Anxiety, and Stress Scale‐21 (DASS‐21); the Perceived Social Support Scale (PSSS); and the Brief Resilience Scale (BRS). Data analysis was conducted using SPSS version 26.0. Statistical methods employed included t‐tests, one‐way analysis of variance (ANOVA), chi‐square tests and Mann–Whitney U‐tests for comparisons between groups. Pearson correlation coefficients were calculated to analyse the relationship between the SRSS score and the DASS‐21, PSSS and BRS scores. A multiple linear stepwise regression analysis was conducted to determine the independent influencing factors of sleep quality. Results More than 90% of the nurses were infected with COVID‐19, and 60.6% had sleep disorders. The regression analysis revealed that anxiety, the BRS score, comorbidities, hospital grade, clinical front‐line, age and COVID‐19 infection independently predicted sleep quality. The scores for several SRSS items were higher than the Chinese norm, especially for the nurses in tertiary hospitals. Patient and Public Contribution No patient or public contribution.